Fetal alcohol syndrome - Nevitt, Amy. (New York Rosen Pub. Group, 1996)
Discusses the dangers of consuming alcohol while pregnant, describes the signs and symptoms of fetal alcohol syndrome, and suggests ways to prevent FAS.
Keywords: Fetal alcohol syndrome -- Juvenile literature